Consumer Perceptions and Preferences of Beverage Products in Malang City - Mohammad Saifur Rohman; Mifetika Lukitasari; Dwi Adi Nugroho; Nashi Widodo; Inggita Kusumastuty; Nur Ida Panca Nugrahini (Budapest International Research and Critics University, 2022)
This research aims to investigate the consumer perceptions and preferences of beverage products in Malang City, East Java. This study uses a Mixing theory approach, which analyzes research data quantitatively by using descriptive analysis, and qualitatively. The population is all consumers of beverage products in Malang city, where 220 consumers were selected as research samples through purposive random sampling. Primary data were collected using a questionnaire. Types of drinks that are commonly consumed by the local community include soft drinks, tea, milk, coffee, health drinks, and beverages included in